Experience of leaving an abusive relationship among women survivors / Ling Mee Chooi - Ling, Mee Chooi (2013)
The purpose of this qualitative study is to explore women survivors’ experiences of leaving an abusive relationship, to examine how they were able to overcome the obstacles of leaving, and how they utilized resources that enabled them to leave. This study also allowed women to express their own opinions about what helped them leave the abusive relationships. As the process of telling their experiences unfolded, it illuminated the reasons why the women left, providing an explanation of specific aspects of the process that made a difference for the women. This research placed emphasis on the actions of abused women and what they did. Rather than examining why a woman stayed in an abusive relationship, the researcher looked at how she actively ended the relationship. The knowledge gained can then be utilized to aid women who are trying to end an abusive relationship. They can be given practical assistance and support using the data gleaned from those women who have already left as they moved through the process of ending the abuse in their lives. This study used a phenomenological approach, and in-depth interviews to gather the stories that provided a rich narrative of each woman’s experience in leaving an abusive relationship. A purposive sampling was used in this study. The total sample consist of seven formerly abused women of diverse races (2 Malays, 3 Chinese, 1 Indian and 1 Punjabi) all of whom are Malaysians and have been out of the relationship for at least a year. This study explored the experience of leaving an abusive relationship. Themes from the analysis of the participant interviews highlight the individual experiences of leaving intimate partner violence as well as the sustaining factors that enabled them to leave permanently. A total of five themes emerged: (a) the experience of abuse; (b) the turning point; (c) factors affecting leaving; (d) the permanent exit; and (e) life after leaving. This study has provided some insights into how the seven survivors who had been abused were able to leave and remain out of their abusive relationships. These survivors accomplished leaving and remaining out of relationship through their courage and awareness, their ability to draw upon the resources available, to rely on their beliefs and remained focus on life after the abuse. All of them found that life after ending the relationship was much happier and they now enjoy a great sense of freedom where the sky is their limit. Far from being passive victims, they are not only survivors but are great warriors in their own right.